Impaired activation of plasmacytoid dendritic cells via toll-like receptor 7/9 and STING is mediated by melanoma-derived immunosuppressive cytokines and metabolic drift - Monti, Matilde; Ferrari, Giorgia; Grosso, Valentina; Missale, Francesco; Bugatti, Mattia; Cancila, Valeria; Zini, Stefania; Segala, Agnese; La Via, Luca; Consoli, Francesca; Orlandi, Matteo; Valerio, Alessandra; et al. (Frontiers in Immunology, 2024)
Plasmacytoid dendritic cells (pDCs) infiltrate a large set of human cancers. IFN-α produced by pDCs induces growth arrest and apoptosis in tumor cells and modulates innate and adaptive immune cells involved in anti-cancer immunity. Moreover, effector molecules exert tumor cell killing. However, the activation state and clinical relevance of pDCs infiltration in cancer is still largely controversial.In Primary Cutaneous Melanoma (PCM), pDCs density decreases over disease progression and collapses in metastatic melanoma (MM). Moreover, the residual circulating pDC compartment is defective in IFN-α production. Here, based on a set of microscopic, functional and in silico analysis, we demonstrated that the melanoma milieu directly impairs type I interferon and CXCL10 production by pDCs via TLR-7/9 and cGAS-STING signaling pathways. Based on bulk transcriptomic data and functional validation, we confirmed that melanoma-derived immunosuppressive cytokines and a metabolic drift represent relevant mechanisms enforcing pDC-mediated melanoma escape. These findings propose a new window of intervention for novel immunotherapy approaches to amplify the antitumor innate immune response in cutaneous melanoma (CM).